2021
DOI: 10.1175/jas-d-21-0082.1
|View full text |Cite
|
Sign up to set email alerts
|

Invented Forces in Supercell Models

Abstract: This paper examines methods used in supercell models to maintain a steady, sheared, horizontally uniform environment with a three-force balance in the planetary boundary layer (PBL) and a two-force balance above it. Steady environments are maintained while ignoring the thermal-wind balance that permits large shear above the PBL. The Taylor-Proudman theorem indicates that wind profiles above the PBL must be unidirectional for balanced environments. In principle, supercell models that do not accommodate thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In [111,112], it is proposed to use a certain fictitious force that creates false (artificial) horizontal vorticity. However, [113] notes that in meteorology, the laws of mass, energy, momentum, angular momentum, and entropy conservation must be inviolable. In [113], it is shown that rapid tornado genesis in modeling can be associated with a combination of the following factors: (1) excessively strong convective initiation in a very unstable atmosphere, which leads to too-strong low-level updraft at the beginning of the supercell's life; (2) the use of a lower boundary condition of semi-slip; (3) the absence of perturbations to excite significant turbulence, which leads to too-strong friction force and too-large shear in a toothin layer near the ground [114]; and (4) the use of omnipresent, all-pervading external force to maintain a stable horizontally homogeneous medium-this force introduces additional degrees of freedom that allow the restrictions of the Taylor-Proudman theorem to be bypassed but leads to changes in the dynamics within the storm.…”
Section: Dynamics Of the Cyclostrophic Balancementioning
confidence: 99%
See 1 more Smart Citation
“…In [111,112], it is proposed to use a certain fictitious force that creates false (artificial) horizontal vorticity. However, [113] notes that in meteorology, the laws of mass, energy, momentum, angular momentum, and entropy conservation must be inviolable. In [113], it is shown that rapid tornado genesis in modeling can be associated with a combination of the following factors: (1) excessively strong convective initiation in a very unstable atmosphere, which leads to too-strong low-level updraft at the beginning of the supercell's life; (2) the use of a lower boundary condition of semi-slip; (3) the absence of perturbations to excite significant turbulence, which leads to too-strong friction force and too-large shear in a toothin layer near the ground [114]; and (4) the use of omnipresent, all-pervading external force to maintain a stable horizontally homogeneous medium-this force introduces additional degrees of freedom that allow the restrictions of the Taylor-Proudman theorem to be bypassed but leads to changes in the dynamics within the storm.…”
Section: Dynamics Of the Cyclostrophic Balancementioning
confidence: 99%
“…In [111,112], it is proposed to use a certain fictitious force that creates false (artificial) horizontal vorticity. However, [113] notes that in meteorology, the laws of mass, energy, Examples of the formation of vortices in high-temperature substances and under the action of a strong magnetic field, as well as under conditions of fast plasma processes, are possible [115][116][117][118].…”
Section: Dynamics Of the Cyclostrophic Balancementioning
confidence: 99%